AKTIVITAS IMMUNOMODULATOR EKSTRAK ETANOL DAUN BABADOTAN [AGERATUM CONYZOIDES (L.)] TERHADAP MENCIT JANTAN GALUR SWISS WEBSTER - Suhendy, Hendy (P3M STIKes Bakti Tunas Husada, 2019)
Hypersensitivity reactions such as anaphylaxis are increase over time. Anaphylaxis generally affects the skin, breathing, cardiovascular and digestive systems. Ageratum conyzoides L. are often used by the people to heal skin diseases, wounds and allergies. The objectives of this study is to determine the immunomodulatory activity of the ethanolic extract of babadotan leaves (ageratum conyzoides L) on male mice using the active cutaneous anaphylactic reaction method. The method is an experimental study of 4 groups each consisting of 4 male swiss webster strain mice. The first step is the process of sensitization of each group for 2 cycles (7 days per cycle). There is not treatment for Group 1 as a normal group, but Group 2 as a negative group, Group 3 as group I test and Group 4 as group II test each are given by ovalbumin (5 ml / kg BW) intraperitoneally. The second stage is challenging on a day before the experiment by shaving the back areas of the mice as the injection areas. Inject intracutaneously in each sector with 0.1 mL of 10% egg white solution (a red bump will form). Fifteen minutes after the formation of the bump, give the ethanol extract of the babadotan leaf (100 mg / Kg BW) to the test group I and the test group II (250 mg / Kg BW). Observe and measure these sectors every 15 minutes for 60 minutes, then continue observations every day for 7 days. Observations include the first time the appearance of bump, diameter of bump after 60 minutes and until the time of bump disappearance. The results showed that the ethanol extract of babadotan leaves test group II ( 250 mg / kg BW) had the best antianaphylactic activity with the possibility mechanism through inhibition on histamine. Keywords: Leaves, Ageratum conyzoides L., Immunomodulatory, active cutaneous anaphylaxis